Sphingosine-1-phosphate synthesis and functions in mast cells. (December 2008) - Price, Megan M; Oskeritzian, Carole A; Milstien, Sheldon; Spiegel, Sarah
Sphingolipids are not only major lipid components of all eukaryotic cell membranes, but they also comprise an important family of bioactive signaling molecules that regulate a diverse array of biological responses. The sphingolipid metabolite sphingosine-1-phosphate (S1P), is a key regulator of immune responses. Cellular levels of S1P are determined by the balance between its synthesis, involving two sphingosine kinases (SphK1 and SphK2), and its degradation, involving S1P lyase and S1P phosphatases. S1P mainly signals through its cell-surface receptors and may also have intracellular functions. S1P has important functions in mast cells – the major effectors of allergic responses. Antigen triggering of IgE receptors on mast cells activates both SphKs resulting in the production of S1P that is released and regulates and amplifies mast cell functions, including degranulation as well as cytokine and chemokine release.